Decision-Making in Educational Leadership: A Philosophical Perspective - Fathia Alya Rosyada; Lucia Rini Sugiarti; Fendy Suhariadi (Jawda: Journal of Islamic Education Management, 2026)
In making decisions in educational leadership, there is a need for a robust philosophical foundation in response to the current complex problems. The purpose of this research is to examine the essence of philosophical views in influencing educational management decision-making processes, uncover the paradigms in ethics, as well as examine the integration between universal philosophical views and Indonesian local wisdom. This study employs a qualitative library research method, collecting data through the identification, selection, and critical review of relevant academic literature published between 2021-2025, which is analyzed using thematic content analysis. The result shows that the integration between universal ethics views (deontology, utilitarianism, or virtue ethics) and local wisdom constructs a foundation in decision-making. Contemporary ethical paradigms transform from hierarchical approaches toward holistic models integrating professional skills, crisis adaptation, and inclusive data-driven decision making. Practical implications demand developing leadership competencies that balance data literacy with emotional intelligence, responsiveness to local contexts, and creating reflective organizational cultures. This study emphasizes the need for transforming educational leader preparation by integrating character development, philosophical reflection, and ethical competencies to produce wise and meaningful decisions. However, this study is limited to secondary data derived from literature sources, which may not fully capture contextual variations in real educational settings. Therefore, future research is encouraged to incorporate empirical field studies to further validate and enrich the proposed philosophical framework.